Lanthanum and zinc incorporated hydrotalcites as solid base catalysts for biodiesel and biolubricants production - Rahul, R.; Satyarthi, Jitendra K.; Srinivas, D. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2011)
Mg-Al hydrotalcites doped with varying amounts of lanthanum and zinc ions (10 30 mol %) have been prepared by co-precipitation method and used, after calcination at 873 K, as solid base catalysts for transesterification of soybean oil with methanol (producing biodiesel) and n-octanol (producing biolubricants). The catalyst with 20 mol % of lanthanum shows the highest transesterification activity (soybean oil conversion = 100 % and biodiesel yield = 95 %) at 423 K in 4 h. Catalytic activity varies in proportion with the basicity of the catalysts.
Keywords: Biodiesel; Biolubricants; catalysis; Doped hydrotalcites; Hydrotalcites; Lanthanum; Solid base catalysts; transesterification; Vegetable oils; zinc

Behavior of the transport and separation of lanthanum, yttrium and lutetium metal ions through a celluose fiber supported solid membrane - Gaikwad, Abaji G. (Macedonian Journal of Chemistry and Chemical Engineering, 2012)
A newly designed membrane cell was used to study the behavior of the transport and separation of lanthanum, yttrium and lutetium metal ions using a cellulose fiber supported solid membrane. The cellulose fiber membrane was prepared by the chemical modification of cellulose fiber using an esterification reaction with citric acid. Different experimental variables were investigated, such as time, membrane size, stirring of the source and receiving phases and the pH of the source phase. The use of different stripping agents in the receiving phase was explored, including nitric acid, hydrochloric acid, sodium nitrate, ammonium thiocyanate, D(2)EHPA, TBP, Aliquat-336, tartaric acid, EDTA and organic solvents. Pre-concentration of lanthanum, yttrium and lutetium metal ions from dilute solutions was carried out.
Keywords: binary mixture; cellulose fiber membrane; Citric acid; complexing reagent; Lanthanum; lutetium; metal ions; Separation; transport studies; yttrium

Methane reforming with carbon dioxide over La-Ni-x-Ce1-x mixed oxide catalysts - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Upendar, K.; Lingaiah, N.; Rao, Kamaraju Seetha Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
La-Ni-x-Ce1-x mixed oxide (0 <= x <= 1) catalysts have been hydrothermally prepared, characterized by physico-chemical techniques and evaluated for CO2 reforming of methane. High conversions are achieved for both methane and carbon dioxide over the LaNi0.6Ce0.4O3 catalyst tested under the conditions of CO2/CH4/N-2 ratio of 80/80/80. (total flow rate = 240 mL/min), space velocity of 28,800 h(-1) and at a temperature of 800 degrees C. The H-2/CO ratio in the syngas is stable at 0.93 +/- 0.02. Exchanging Ni with Ce, rather than with La as reported in the literature, appears to be a better option for the improved performance of the catalysts.
Keywords: Carbon dioxide reforming; Catalysts; Cerium; Dry reforming; Hydrothermal synthesis; Lanthanum; Methane reforming; Mixed oxides; Nickel